2008
DOI: 10.1016/j.jtcvs.2007.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Is minimally invasive harvesting of the great saphenous vein for coronary artery bypass surgery a cost-effective technique?

Abstract: Minimally invasive harvesting is the most cost-effective method of harvesting the great saphenous vein and can significantly improve a patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 18 publications
(80 reference statements)
2
28
0
1
Order By: Relevance
“…In contrast to EVH when significant decrease of wound-healing complications, in-hospital stay, and need for further out patient care support its cost-effectiveness, it remains questionable whether reduction of neurological impairment and better cosmetic results outweigh the cost of ERAH, particularly if single use devices are employed 29 . We are aware that there was only a total of 91 RAs harvested (54.9% endoscopically) during the tracking period.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to EVH when significant decrease of wound-healing complications, in-hospital stay, and need for further out patient care support its cost-effectiveness, it remains questionable whether reduction of neurological impairment and better cosmetic results outweigh the cost of ERAH, particularly if single use devices are employed 29 . We are aware that there was only a total of 91 RAs harvested (54.9% endoscopically) during the tracking period.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have investigated the short-term cost-effectiveness of EVH or minimal invasive vein harvesting compared to OVH [4,5]. Rao et al performed decision analytic modeling and estimated that minimal invasive vein harvesting was cost-effective compared to conventional harvesting within six weeks postoperatively [5].…”
Section: Discussionmentioning
confidence: 99%
“…Rao et al performed decision analytic modeling and estimated that minimal invasive vein harvesting was cost-effective compared to conventional harvesting within six weeks postoperatively [5]. In a costeffectiveness analysis alongside a randomized trial, Oddershede et al concluded that EVH was not cost-effective compared to OVH within the first five weeks postoperatively [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the effect of MIVH on patient morbidity from wound-related complications has been extensively investigated in the literature, the effect on the quality of the harvested conduit is less clear [1,2]. However, before attempting this comparison, it is important to consider the characteristics that would be expected of a high-quality conduit, namely its macroscopic appearance, histologic quality (with particular regard to endothelial continuity), functional characteristics, and mid-term and long-term patency [3].…”
Section: Invited Commentarymentioning
confidence: 99%